ANALISIS HASIL VALIDITAS E-MODUL INTERAKTIF PADA MATERI IKLIM DAN PERUBAHANNYA UNTUK SISWA KELAS IV SEKOLAH DASAR - Awaliya, Nabila; Nurani, Dwi Cahaya; Susiloningsih, Esti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is an R&D research with the ADDIE model which aims to determine the validity or feasibility of the interactive e-module based on flipbooks on climate and its changes. The results of this study are that the feasibility validation by material experts is 90%